(untitled) (Revista científica Olimpia, 2026)
The first men’s beach volleyball world championship was practiced in 1987 at post 11 on Ipanema beach, in the state of Rio de Janeiro, located in the southeastern region of Brazil. This world championship had the participation of 20 doubles from various countries (United States of America, Brazil, Italy, Japan, Chile, Argentina, and Mexico). This first world doubles beach volleyball championship was dominated by American doubles because that nation had a professional beach volleyball program. But the Brazilian doubles well in championship, finishing in 3rd and 4th place. The top three doubles in the first Beach Volleyball World Championship started playing in the quarterfinals (a total of 5 matches, and an average of 4.50 matches), playing fewer matches than the doubles that started playing in the group stage (a total of 6 and 8 matches, and an average of 6.50 matches). The independent “t” test detected a statistically significant difference [t (6) = -2.82, p = 0.03*] in the number of matches by doubles that started the competition in the quarterfinals versus doubles from the group stage. In conclusion, a detailed study of the championship table and performance data of sand volleyball doubles is important for understanding why certain teams performed better and worse.